In vitro assessment of the immunomodulatory effects of probiotic Bacillus strains on chicken PBMCs - Larsberg, Filip; Sprechert, Maximilian; Hesse, Deike; Falker-Gieske, Clemens; Loh, Gunnar; Brockmann, Gudrun A.; Kreuzer-Redmer, Susanne (Frontiers in Immunology, 2024)
The beneficial effects of feeding probiotic Bacillus subtilis DSM 32315 (BS) and Bacillus velezensis CECT 5940 (BV) to chickens in vivo are well-documented, with potential immune modulation as a key mechanism. In this study, we investigated the direct interactions of chicken peripheral blood mononuclear cells (PBMCs) with BS or BV in vitro through whole transcriptome profiling and cytokine array analysis. Transcriptome profiling revealed 20 significantly differentially expressed genes (DEGs) in response to both Bacillus treatments, with twelve DEGs identified in BS-treated PBMCs and eight in BV-treated PBMCs. Pathway analysis using the Kyoto Encyclopedia of Genes and Genomes (KEGG) indicated significant regulation of immune-related pathways by both BS and BV. Notably, BS treatment upregulated genes associated with immune cell surface markers (CD4, CD25, CD28), anti-inflammatory cytokine interleukin-10 (IL-10), and C-C motif chemokine ligand 5 (CCL5), while downregulating pro-inflammatory IL-16. BV treatment similarly affected the immune cell surface markers, IL-16, and CCL5 expression, with no impact on IL-10 expression. Both treatments induced higher expression of avian β-defensin 1 (AvBD1). The results of this in vitro study indicate an immunomodulatory effect of BS and BV in chicken PBMCs by regulating genes involved in anti-inflammatory, bacteriostatic, protective, and pro-inflammatory responses. Consequently, BS and BV may serve to augment the immune system's capacity to defend against infection by modulating immune responses and cytokine expression.Thus, the administration of these probiotics holds promise for reducing reliance on antimicrobials in farming practices.